SMALL AND MEDIUM ENTERPRISES; WHERE DOES ALBANIA STAND? - Çela, Mirësi; Gaspari, Alda (European Scientific Journal, ESJ, 2015)
Small and Medium Enterprises are vital for economic growth and development in both industrialized and developing countries. They provide the majority of jobs and create new ones, they have the biggest share in added value, turnover, profit, and in the most developed economies in exports. The purpose of this paper is to give information on Small and Medium Enterprises (SMEs) in Albania. Where does Albania stand, how competitive is the economy, what has accomplished so far and what need to be done further. By answering how the Albanian Government promotes their development and what reforms are undertaken to make the business climate more friendly, the conclusion provides some recommendations.